The impact of Thatcherite social and economic policies on the lives of British people 1958-2012 - Gray, Emily (UK Data Service, 2020)
As part of a project exploring the impact of Thatcherite social and economic policies on the lives of British people, we have merged together key variables from the British Cohort Study so that longitudinal data analyses over several years and decades are more easily available. The variables included relate to housing, schooling, employment, offending and victimisation, welfare, social and political attitudes and similar variables. This exercise was repeated for the National Child Development Study so as to provide a point of comparison. The data are not being made available here, but we have provided a narrative count of how we merged these two longitudinal data sets so that each data set had a longitudinal version of some of the data from birth to the year 2012. This grant follows on from two earlier ESRC-funded grants held by Stephen Farrall, and a British Academy seminar he co-organised with Colin Hay (a leading theorist of Thatcherism). The first grant was a scoping project, which assessed the extent to which it was possible to undertake more prolonged and in-depth investigations into the social, economic and cultural impacts of Thatcherite public policy on contemporary UK society, especially as these features relate to criminal justice policy. This earlier grant concluded that it was possible to undertake two further projects. The first of these (looking at regional level changes using repeated cross-sectional surveys) we have, with ESRC-funding, completed. The second project (and the one we are seeking funding for herein) would extend this enquiry to the individual level using longitudinal data (thereby ensuring that we do not fall foul of committing the ecological fallacy - that is assuming that because something operates at the national level, it also works in the same way for individuals). To do this we will use data from the British Cohort Study which is a longitudinal study of a group of men and women born in one week in 1970. The cohort (which numbers over 17,000 people) have been interviewed themselves on a number of times (at ages 10, 16, 21, 26, 29, 34, 38 and 42) and there have been interviews with their mothers and teachers when they were younger. They were asked a range of questions about their home lives, schooling, employment careers, social attitudes and, crucially for us, since we are interested in how these processes lead people to or away from crime, their victimisation, drug taking, arrest history and offending. We have spent a long time theorising how the social and economic policies of the 1980s and 1990s might have operated to alter the social environments in which these young people grew up. Moreover, our analyses of changes in social attitudes in the country at the time and the extent to which these may have differed between generations allows us to 'locate' this cohort's experiences and values in wider contexts. By relying, where and when appropriate to do so, on a similar cohort study which went before this one (the National Child Development Study, participants born in 1958), we can disentangle the complex changes which occur as people age. This means that we are much less likely to misinterpret what looks like significant changes, but which are just a facet of aging and 'growing up'.